Participação do hormônio Triodotironina (T3) no desenvolvimento inicial do matrinxã (Brycon cephalus) - Vasques, Lucia Helena [UNESP] (2003)
The present work evaluated the effect of the exposure of matrinxã (Brycon cephalus) eggs to triiodothyronine (T3) on the embrionic development. The study was performed at the Centro Nacional de Pesquisa em Peixes Tropicais (CEPTA/IBAMA), Pirassununga, SP, and Departamento de Morfologia e Fisiologia Animal, Faculdade de Ciências Agrárias e Veterinárias, UNESP, Jaboticabal campus, SP. Fertilized eggs were exposed to 0.00; 0.01; 0.05 e 010ppm T3 and samplings were carried out at each 15 minutes during the first 2 hs after the fertilization and following at each 30 minutes to observation in stereomicroscopy. Hatching rate and eggs counting were done to qualify the biological material. Eggs (50 per female) were spheric, average diameter of 912.5 ± 15.31 μm regardless the treatment. After fertilization, it was possible to observe the germinative disk at animal pole, what characterize the eggs as telolecits and polilecits due to the great amont of yolk, and partial cleavage, or meroblastic cleavage occurring only in the animal pole. The embrionic development of matrinxã occurred at 27oC in intervals of 12hs in the control group (0ppm T3) and 0.1ppm group, 12:30hs in the 0.05ppm group and 13hs in the 0.01ppm group. The hatching rate showed that the exposure of the eggs to triiodothyronine did not affect the number of viable and dead larvae. Besides eggs exposed to 0.01ppm T3 produced higher number of abnormalities